Meta-Analysis of the Role of Intermittent Pneumatic Compression of the Lower Limbs to Prevent Venous Thromboembolism in Critically Ill Patients. (March 2022) - Haykal, Tarek; Zayed, Yazan; Dhillon, Harsukh; Miran, Muhammad Shah; Kerbage, Josiane; Bala, Areeg; Samji, Varun; Deliwala, Smit; Bachuwa, Ghassan
Critically ill patients (patients treated in a medical or surgical intensive care unit) are at high risk of venous thromboembolism (VTE) development (deep vein thrombosis [DVT] and/or pulmonary embolism). Multiple thromboprophylaxis strategies have been used for the prevention of VTE in this population with various outcomes. Therefore, we aimed to evaluate the efficacy of intermittent pneumatic compression (IPC) prophylaxis in the lower limb compared with no treatment, anticoagulant use, or their combinations in reducing risk. A comprehensive electronic database search was conducted for all randomized clinical trials (RCTs) comparing the clinical outcomes of IPC versus anticoagulants or no treatment or their combinations for the prevention of VTE for critically ill patients. The primary outcome was VTE. The secondary outcome was DVT. We performed a Bayesian network meta-analysis to calculate odds ratios (ORs) and 95% credible intervals (CrIs). We included 5 RCTs with 3133 total patients, represented by a mean age of 49.61 ± 18 years, while 60.28% were male. There was a significant reduction of the primary outcome (incidence of VTE events) when no treatment was compared with IPC (OR = 0.36; 95% CrI = 0.18-0.71), anticoagulation alone (OR = 0.30; 95% CrI = 0.12-0.68), or anticoagulation with IPC (OR = 0.34; 95% CrI = 0.13-0.81). In addition, there was a significant reduction in DVT when no treatment was compared with IPC (OR = 0.45; 95% CrI = 0.21-0.9), anticoagulation alone (OR = 0.16; 95% CrI = 0.03-0.66), or anticoagulation with IPC (OR = 0.18; 95% CrI = 0.03-0.84). However, there were no significant differences between other comparisons (IPC vs anticoagulation alone, anticoagulation alone vs anticoagulation with IPC, or anticoagulation with IPC vs IPC alone) regarding VTE or DVT incidence. Among critically ill patients, IPC alone, anticoagulation alone, and IPC with anticoagulation were associated with a significant reduction of VTE and DVT incidence compared with no treatment. However, there was no significant difference between these modalities when compared together. Therefore, further larger studies comparing those different thromboprophylaxis modalities and their combinations are needed to provide more robust results for future clinical recommendations.